2020
DOI: 10.3389/fcell.2020.00157
|View full text |Cite
|
Sign up to set email alerts
|

Human Derived Immortalized Dermal Papilla Cells With a Constant Expression of Testosterone Receptor

Abstract: Androgenetic alopecia (AGA) is the most common type of hair loss, and is mainly caused by the biological effects of testosterone on dermal papilla cells (DPCs). In vitro culturing of DPCs might be a useful tool for the screening of target molecule of AGA. However, primary DPCs cannot continuously proliferate owing to cellular senescence and cell culture stress. In this study, we introduced mutant cyclin-dependent kinase 4 (CDK4), Cyclin D1, and telomerase reverse transcriptase (TERT) into DPCs. We confirmed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Although the exact mechanism is unclear, the endogenous AR expression level became lower after several passages of DPCs (Kwack et al, 2008). In agreement with previous reports of AR suppression, we also detected downregulation of AR in DPCs immortalized using the K4DT method (Fukuda et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Although the exact mechanism is unclear, the endogenous AR expression level became lower after several passages of DPCs (Kwack et al, 2008). In agreement with previous reports of AR suppression, we also detected downregulation of AR in DPCs immortalized using the K4DT method (Fukuda et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…As shown in Figure S1, although the efficiency of gene introduction was only around a few percent, by selecting the successfully introduced cells using antibiotics (G418 for SV40, hygromycin for E6/E7), we successfully established human DPCs that expressed SV40 or E6/E7. We previously reported the establishment of immortalized DPCs with combinatorial expression of R24C mutant cyclin-dependent kinase 4 (CDK4), cyclin D1, and telomerase reverse transcriptase (TERT) (Fukuda et al, 2020). Hereafter, we will refer to immortalized cells with the combinatorial expression of R24C mutant CDK4, cyclin D1, and TERT as K4DT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the gene networks controlled by testosterone, especially in dermal papilla cells (DPCs) are not fully understood. Interestingly, we accidentally found that the expression of AR is strongly suppressed even in the early passage of human DPCs 3 . The suppression of AR gene expression under the cultured cell conditions of DPCs has been previously reported in rat-derived DPCs, which is consistent with our finding 4 .…”
Section: Background and Summarymentioning
confidence: 95%